Correspondance 1916-1955 : commentée par Max Born / Albert Einstein, Max Born, Hedwig Born ; int. de Lord Bertrand Russell ; pref. de Werner Heisenberg - Einstein, Albert (1879-1955)
Tít. de la cub. : Albert Einstein/Max Born Briefwechsel 1916-1955